2019
DOI: 10.4300/jgme-d-19-00248.1
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Programs Affected by Resident Attrition and Program Factors Associated With Attrition in Emergency Medicine

Abstract: Background Resident attrition negatively affects residents and programs. The incidence of attrition in emergency medicine (EM) and program-specific factors associated with attrition remain unclear. Objective We quantified the percentage of EM residencies affected by attrition between 2007 and 2016 and identified program-specific factors associated with attrition. Methods We performed a retrospective analysis of data derived from the American Medical Association National Graduate Medical Education Census. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Comparably, Brockberg et al reported that 23% of EM programs experienced attrition each year and more than 80% experienced attrition over the 10-year period of 2007–2016. 1 Our data is consistent with existing studies demonstrating that while the overall incidence of resident attrition in EM on an individual level is low, a substantial portion of training programs are impacted.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Comparably, Brockberg et al reported that 23% of EM programs experienced attrition each year and more than 80% experienced attrition over the 10-year period of 2007–2016. 1 Our data is consistent with existing studies demonstrating that while the overall incidence of resident attrition in EM on an individual level is low, a substantial portion of training programs are impacted.…”
Section: Discussionsupporting
confidence: 90%
“…Resident attrition is often defined as the premature loss of a resident prior to completion of training. 1 , 2 Attrition has the potential to negatively impact fellow trainees and program leadership. 3 6 It can harm future recruitment efforts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual annual rate of attrition for EM residents is approximately 0.8%. [45][46][47] Potential barriers to attrition include student debt, lack of other employment options, and the opportunity cost of leaving the field of medicine. Furthermore, even though most residents train within academic institutions, over a third of EM residents in our study reported that they did not wish to pursue academic medicine, with burnout and professional fulfillment being strong drivers of these plans.…”
Section: Discussionmentioning
confidence: 99%
“…One might say that these two de nitions could be linked together, as can be seen in the case of residency programs. Attrition is a major concern for any residency program, as it not only hinders the process of training but also negatively affects all those involved (9,10,11). Some of the side effects of attrition include disruption of schedules, add-on workload on the remaining trainees, compromised service provision, and the greater problem of hiring a replacement (12).…”
Section: Introductionmentioning
confidence: 99%